2021
DOI: 10.1101/2021.07.04.21259985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 Vaccination in Pregnancy: A Systematic Review

Abstract: Objective: Pregnancy is a risk factor for severe Covid-19. Looking for safe vaccines that evoke protective maternal and fetal antibody response is important. Methods: We searched from registries (ClinicalTrials.gov, the WHO Clinical Trial Registry, and the EU Clinical Trial Registry) and databases (MEDLINE, ScienceDirect, Cochrane Library, Proquest, and Springer) up until June 20, 2021. Articles were selected based on inclusion and exclusion criteria after duplicates were removed. Infection rate, maternal anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
(110 reference statements)
1
10
0
Order By: Relevance
“…A bigger study that took place in the US reviewed the safety of mRNA vaccination against SARS-CoV-2 during all trimesters of pregnancy, or just before conception [ 30 ]. They reported that the distribution of negative pregnancy and birth complications such as fetal loss, preterm birth, small size for gestational age, congenital abnormalities, and stillbirths among participants with completed pregnancies was comparable to previously published rates in pregnant populations studied prior to the COVID-19 pandemic [ 31 , 32 , 33 ]. The largest study to date included a review of almost fifty thousand pregnant women who received mRNA vaccines for COVID-19.…”
Section: Discussionsupporting
confidence: 69%
“…A bigger study that took place in the US reviewed the safety of mRNA vaccination against SARS-CoV-2 during all trimesters of pregnancy, or just before conception [ 30 ]. They reported that the distribution of negative pregnancy and birth complications such as fetal loss, preterm birth, small size for gestational age, congenital abnormalities, and stillbirths among participants with completed pregnancies was comparable to previously published rates in pregnant populations studied prior to the COVID-19 pandemic [ 31 , 32 , 33 ]. The largest study to date included a review of almost fifty thousand pregnant women who received mRNA vaccines for COVID-19.…”
Section: Discussionsupporting
confidence: 69%
“…A systematic review on COVID‐19 vaccination in pregnancy was recently published on MedRxiv 38 . That review limited their analysis to pregnant populations and included 12 observational studies, two of which were not included here because they had less than 10 participants.…”
Section: Discussionmentioning
confidence: 99%
“…Following these vaccinations, most pregnant females showed injection‐site pain/soreness, headache, fatigue, chills, fever, myalgia, and nausea. 67 …”
Section: Efficacy Of Covid‐19 Vaccines Among Children Teens and Pregn...mentioning
confidence: 99%